Utilization of Mineral Wools as Alkali-Activated Material Precursor - Yliniemi, Juho (Materials (Basel), 2016)
Mineral wools are the most common insulation materials in buildings worldwide. However, mineral wool waste is often considered unrecyclable because of its fibrous nature and low density. In this paper, rock wool (RW) and glass wool (GW) were studied as alkali-activated material precursors without any additional co-binders. Both mineral wools were pulverized by a vibratory disc mill in order to remove the fibrous nature of the material. The pulverized mineral wools were then alkali-activated with a sodium aluminate solution. Compressive strengths of up to 30.0 MPa and 48.7 MPa were measured for RW and GW, respectively, with high flexural strengths measured for both (20.1 MPa for RW and 13.2 MPa for GW). The resulting alkali-activated matrix was a composite-type in which partly-dissolved fibers were dispersed. In addition to the amorphous material, sodium aluminate silicate hydroxide hydrate and magnesium aluminum hydroxide carbonate phases were identified in the alkali-activated RW samples. The only crystalline phase in the GW samples was sodium aluminum silicate. The results of this study show that mineral wool is a very promising raw material for alkali activation.